What's up with WAC? Archaeology and 'engagement' in a globalized world - Shepherd, Nick (2011)
The year 2011 marks the twenty-fifth anniversary of the World Archaeological Congress (WAC). WAC marked a bold intervention in the politics of knowledge in archaeology in the context of the mid-1980s. But how has it fared in contemporary worlds of practice? In this paper, two senior WAC members take a close and critical look at the changing fortunes, meanings, and contexts of the organization. At its centre, is an account of the controversial meeting between the WAC Executive and Rio Tinto Limited, the mining multinational, in Melbourne in 2007. Other parts of the paper engage with notions of the Indigenous, and discuss the assumptions informing the WAC programme Archaeologists Without Borders. Framed as a challenge, the paper invites response and commentary, as a way of opening debate which allows us to envisage alternative futures for the discipline, beyond the banal prospect of 'Archaeology Inc.'.